Analysis for Organochlorine Pesticide Residues in Honey from Kabale District, South-Western Uganda - Ntirushize, Benon; Wasswa, John; Ntambi, Emmanuel; Christopher, Adaku (American Journal of Analytical Chemistry, 2019)
This study was motivated by the reported accumulation of Organochlorine Pesticides (OCPs) residues in the various environmental matrices within Uganda, resulting from their use in agriculture and health sectors. This raised a concern of the likelihood of the accumulation of the OCPs residues in the honey produced within the country which would affect its purity as well as quality and consequently its competition on the world market. Sixty representative honey samples were collected from selected local beekeepers from four sampling stations in Muko sub-county, Kabale, and extracted for OCPs using a solid-phase procedure followed by a florisil column packed clean-up method and Gas Chromatography-Electron Capture Detector (GC-ECD) analysis. Confirmation of the selected samples was done using an Agilent (6890N, USA) gas chromatograph combined with a mass spectrometer. Recoveries of spiked samples ranged from 71% to 96%, except for pp-DDE (54%), with relative standard deviations from 2% to 14% in terms of repeatability, and from 4% to 17% in terms of reproducibility. Limits of quantification were from 0.003 to 0.1 mg∙kg−1. Endosulfan sulfate was the most frequently detected in 38% of the samples, followed by HexaChloroBenzene (Lindane) in 21% of the samples. Residues of DDT and their metabolites were detected in 17% of the samples. Mean concentrations of the pesticide residues detected range from ND (notdetected) to 1.53 μg/Kg. The acceptable Maximum residual limits (MLRs) are 200 - 300 μg∙kg−1 fresh weight for dieldrin, 500 μg∙kg−1 for DDT and break down products, and 50 μg∙kg−1 wet weight for Lindane (WHO/FAO 2011). Results indicate that the levels of OCP residues detected in honey from the country’s South Western District of Kabale were within the acceptable limits, and hence this honey was safe for human consumption
Keywords: Persistent Organic Pollutants; Organochlorine Pesticides; Metabolites; Kabale District; Honey